A Primeron Fiscal Analysis in Oil-Producing Countries - Medas, Paulo (IMF Working Papers; Working Paper ;, 2009)
This paper proposes an integrated approach to fiscal policy analysis in oil producing countries (OPCs) geared towards addressing their unique and complex policy challenges. First, an accurate assessment of the fiscal stance in OPCs can be obscured by large and volatile oil revenue flows. Second, uncertain and volatile oil revenue flows can complicate the management of macroeconomic policies in these countries. Third, given the exhaustibility of oil reserves, OPCs need to address longer-term sustainability and intergenerational equity issues. The use of non-oil fiscal indicators, stress tests, medium-term frameworks, and permanent oil income models can greatly aid in addressing these challenges.